ANALYSIS OF IMPROVING LEARNING OUTCOMES AND STUDENT RESPONSES TAUGHT USING HOTS CHEMISTRY TEACHING MATERIALS BASED ON THE CASE METHOD ON SOLUTION MATERIAL - Haqqi Annazili Nasution; Ayi Darmana; Jasmidi Jasmidi (UNIVERSITAS NEGERI MEDAN, 2023)
This research aims to analyze the improvement in student learning outcomes and the responses of students who are taught using HOTS (Higher Order Thinking Skill) teaching materials based on the case method in solution material. This research was conducted on students of the chemistry education study program in the chemistry department, FMIPA, Medan State University. Research sampling was carried out using purposive sampling and a sample class of PSPK 23 A was obtained. The research instrument used in this research used test instruments to analyze improvements in learning outcomes and non-test instruments to analyze students' responses to the teaching materials used. The analysis technique for improving learning outcomes is carried out using the N-Gain test and to analyze student responses using a percentage scale. Based on the analyzed learning outcomes data, it was found that the increase in learning outcomes for students in the